2014
DOI: 10.4103/0300-1652.144701
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of malaria in febrile children in Sokoto, Nigeria

Abstract: Background:Presumptive diagnosis of malaria is widespread, even where microscopy is available. As fever is very nonspecific, this often leads to over diagnosis, drug wastage and loss of opportunity to consider alternative causes of fever, hence the need to improve on the clinical diagnosis of malaria.Materials and Methods:In a prospective cross-sectional comparative study, we examined 45 potential predictors of uncomplicated malaria in 800 febrile children (0-12 years) in Sokoto, Nigeria. We developed a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The prevalence of asymptomatic malaria in Nigeria has been reported to range from 25% [18] to 59% [19, 20] in some regions of the country. Asymptomatic infection is an important obstacle in malaria control since such asymptomatic carriers do not seek treatment and thereby remain reservoirs for the life cycle of the infection to continue.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of asymptomatic malaria in Nigeria has been reported to range from 25% [18] to 59% [19, 20] in some regions of the country. Asymptomatic infection is an important obstacle in malaria control since such asymptomatic carriers do not seek treatment and thereby remain reservoirs for the life cycle of the infection to continue.…”
Section: Introductionmentioning
confidence: 99%
“…This may mean that fever is a possible sensitive clinical case definition for malaria. Singh in Sokoto also reported a lower prevalence of 56% (Singh et al, 2014) during the dry season which corresponded to period of low malaria transmission.…”
Section: Discussionmentioning
confidence: 92%
“…A study conducted in southeastern Nigeria found that 86% of caregivers diagnosed malaria mainly by noticing fever, headache, cough, and pains [ 16 ]. A study in Sokoto State examined 800 febrile children who were presumed to have malaria and found that only 56% had confirmed malaria while the remaining 44% were misdiagnosed and treated for malaria [ 17 ]. In Borno State, 310 febrile patients were tested and only 1% were positive for malaria.…”
Section: Essaymentioning
confidence: 99%